A practical approach to bladder preservation with hypofractionated radiotherapy for localised muscle-invasive bladder cancer. (November 2021) - Portner, R.; Bajaj, A.; Elumalai, T.; Huddart, R.; Murthy, V.; Nightingale, H.; Patel, K.; Sargos, P.; Song, Y.; Hoskin, P.; Choudhury, A.
Highlights: Trimodality treatment has similar outcomes to radical cystectomy for invasive bladder cancer. Hypofractionation is recommended over standard fractionation due to superior local control. Dose constraints for hypofractionation include rectal of V50 < 50% and small bowel of V50 < 98 cc. Radiosensitisation with chemotherapy of CON improves radiotherapy outcomes. Adaptive radiotherapy techniques can improve tumour coverage and reduce PTV volumes. Abstract: Bladder preservation with trimodality treatment (TMT) is an alternative strategy to radical cystectomy (RC) for the management of localised muscle invasive bladder cancer (MIBC). TMT comprises of transurethral resection of the bladder tumour (TURBT) followed by radiotherapy with concurrent radiosensitisation. TMT studies have shown neo-adjuvant chemotherapy with cisplatin-based regimens is often given to further improve survival outcomes. A hypofractionated radiotherapy regimen is preferable due to its non-inferiority in local control and late toxicities. Radiosensitisation can comprise concurrent chemotherapy (with gemcitabine, cisplatin or combination fluorouracil and mitomycin), CON (carbogen and nicotinomide) or hyperthermic treatment. Radiotherapy techniques are continuously improving and becoming more personalised. As the bladder is a mobile structure subject to volumetric changes from filling, an adaptive approach can optimise bladder coverage and reduce dose to normal tissue. Adaptive radiotherapy (ART) is an evolving field that aims to overcome this. Improved knowledge of tumour biology and advances in imaging techniques aims to further optimise and personalise treatment.